PENGARUH MODEL PEMBELAJARAN STEM TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA PADA SISWA SMP NEGERI 1 MEGAMENDUNG KABUPATEN BOGOR - Rifani Priharyanti; Atiyani; Irman; Nur Hadi; Rosynanda Nur Fauziah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The purpose of this study was to determine whether the mathematical concept understanding of eighth-grade students at SMP Negeri 1 Megamendung who were taught using the STEM learning model was higher than that of students taught using the direct instruction model. This research is a quasi-experimental study with a non-equivalent control group design, conducted at SMP Negeri 1 Megamendung during the 2025/2026 academic year. The sampling technique used was cluster random sampling, with class VIII A serving as the experimental class and class VIII B as the control class. Data collection techniques included tests, observation, and questionnaires. Data analysis techniques utilized descriptive analysis and inferential analysis with the aid of the SPSS 20 for Windows program. Based on the results of the descriptive and inferential analysis, it was concluded that the mathematical concept understanding of students taught using the STEM learning model was categorized as good, the mathematical concept understanding of students taught using the direct instruction model was categorized as sufficient, and the mathematical concept understanding of students taught using the STEM learning model was higher than that of students taught using the direct instruction model.